2020
DOI: 10.3389/fphys.2020.564604
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Roles of Related Long Non-coding RNAs in the Process of Atherosclerosis

Abstract: Atherosclerosis (AS) is the main cause of coronary heart disease, cerebral infarction, and peripheral vascular disease, which comprise serious hazards to human health. Atherosclerosis is characterized by the deposition of lipids on the interior walls of blood vessels, causing an inflammatory response of immune cells, endothelial cells, and smooth muscle cells, and a proliferation cascade reaction. Despite years of research, the underlying pathogenesis of AS is not fully defined. Recent advances in our understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 93 publications
0
23
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) belong to the large family of ncRNAs, and are involved in many biological processes, such as cell migration, proliferation, cell cycle, apoptosis, and autophagy [ 1 , 2 , 3 ], and in numerous human diseases [ 4 , 5 , 6 , 7 ]. Many studies have also found that they play a main role in tumor initiation promotion and progression, and in drug resistance mechanisms [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) belong to the large family of ncRNAs, and are involved in many biological processes, such as cell migration, proliferation, cell cycle, apoptosis, and autophagy [ 1 , 2 , 3 ], and in numerous human diseases [ 4 , 5 , 6 , 7 ]. Many studies have also found that they play a main role in tumor initiation promotion and progression, and in drug resistance mechanisms [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports that lncRNAs exert their biological effects by regulating the transcription of nearby protein-coding genes(Meng et al, 2020). Considering that the TMOD4 and LEPIS are both located on chromosome 1 with a portion of LEPIS overlapping with the 5′ portion of TMOD4 (Supplementary Figure 1) and that LEPIS and TMOD4 have the same effect on cholesterol homeostasis and AS, we further verified whether LEPIS regulates the expression of TMOD4 .…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence indicates that lncRNAs can modulate gene expression via diverse mechanisms and contribute to the development of various diseases. Some lncRNAs have been demonstrated to work as regulators of the key steps in the progression of atherosclerosis, and these steps include cholesterol metabolism, the inflammation cascade, and apoptosis (Meng, Pu et al, 2020). However, there are still many lncRNAs that urgently need to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of lncRNAs that have been identified and characterized have been in diseases. This include cancers (Jin et al, 2020;Teppan et al, 2020;Zhou et al, 2020;Katsushima et al, 2021), diabetes (Taheri et al, 2020;Xu E. et al, 2020;Ismail et al, 2021), cardiovascular diseases (Fang et al, 2020;Meng et al, 2020;Yeh et al, 2020) and ischemic stroke (Gan et al, 2021;Wolska et al, 2021). In this section, we will focus on angiogenic lncRNAs enriched in disease and their epigenetic functions.…”
Section: Angiogenic Lncrnas In Diseasementioning
confidence: 99%